2014
DOI: 10.1093/heapol/czu078
|View full text |Cite
|
Sign up to set email alerts
|

The role of leadership in people-centred health systems: a sub-national study in The Gambia

Abstract: Recently, increasing attention has been given to behavioural and relational aspects of the people who both define and shape health systems, placing them at the core. A growing refrain includes the assertion that important decisions determining health system performance, including agenda setting, policy formulation and policy implementation, are made by people. Within this actor-oriented approach, good leadership has been identified as a key contributing factor in health systems strengthening. However, leadersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 27 publications
1
22
0
2
Order By: Relevance
“…While the topic of leadership within health systems is under-researched, recent studies have highlighted the multi-polar networks and complex 'organizational ecology' within which leaders are embedded, which support such brokerage processes (Chigudu et al, 2014).…”
Section: Professional Perspectives About the Way Partnership Workmentioning
confidence: 99%
“…While the topic of leadership within health systems is under-researched, recent studies have highlighted the multi-polar networks and complex 'organizational ecology' within which leaders are embedded, which support such brokerage processes (Chigudu et al, 2014).…”
Section: Professional Perspectives About the Way Partnership Workmentioning
confidence: 99%
“…Health systems governance is currently a critical concern in many countries because of increasing demand to demonstrate accountability in the health sector[ 1 – 3 ]. Research has shown that the modes of leadership and management may influence health outcomes such as life expectancy at birth, child mortality, maternal mortality, and self-reported health status.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the infant mortality rate has declined from 59.6 per 1,000 live births in 2009 to 36.5 per 1,000 live births in 2019 [10]. Some studies have shown that the bottlenecks in the performance of health systems can be solved by building competencies of health workers related to leading, managing and governing practices [3,6,[11][12][13][14][15]. Therefore, Ethiopia has adopted and implemented LMG interventions to strengthen its health system and build services that are accessible to more people by developing inspired and inspiring leaders, establishing sound management systems, and ensuring transparent practices within and among individuals, networks, organizations, and governmental bodies.…”
Section: Introductionmentioning
confidence: 99%